1993
DOI: 10.1002/art.1790060206
|View full text |Cite
|
Sign up to set email alerts
|

Use of self ‐ administered joint counts in the evaluation of rheumatoid arthritis patients

Abstract: The validity and reliability of self‐administered joint counts are reported in a group of32 rheumatoid arthritis patients being followed at a university‐based practice located in theSoutheast region of the United States, serving low to middle income urban and rural patients. Adequate inter‐rater reliability among the patients' and the research assistant's joint counts was obtained for upper (r = 0.74), lower (r = 0.96), and upper and lower extremities (r = 0.89). Convergent validity correlations for pain, help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
1
12
1
Order By: Relevance
“…A high level of agreement (Pearson r = 0.89) between joint scores of patients and assessors was also found in another study with the same graded self-report index of joint tenderness [3]. In this study, high correlations were found between both patients' and assessors' joint scores and self-report assessments of pain and learned helplessness (Pearson r's ranging from 0.50 to 0.73) [3].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…A high level of agreement (Pearson r = 0.89) between joint scores of patients and assessors was also found in another study with the same graded self-report index of joint tenderness [3]. In this study, high correlations were found between both patients' and assessors' joint scores and self-report assessments of pain and learned helplessness (Pearson r's ranging from 0.50 to 0.73) [3].…”
Section: Discussionsupporting
confidence: 60%
“…Four studies [2,3,5,6] have not evaluated test-retest reliability; this study and two others [1,4] have evaluated test-retest reliability, and found it to be good. In some studies [1][2][3] a high agreement between patients' self-report joint scores and physician derived scores was found, while in this study and others [4,5] only a low to moderate agreement was found. In two studies [2,3] the self-report joint scores were not validated against laboratory measures of disease activity.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…RADAI scores are correlated significantly with tender and swollen joint counts in rheumatoid arthritis (RA) patients (3)(4)(5)(6)(7). Although developed initially for RA, the authors suggested that the RADAI could be informative in patients with other rheumatic diseases.…”
Section: Introductionmentioning
confidence: 99%